2016
DOI: 10.1097/mjt.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Opioid Abuse/Dependence and Outcomes in Hospitalized Heart Failure Patients

Abstract: Opioid use is associated with unintentional and intentional overdose and is one of the leading causes of emergency room visits and accidental deaths. However, the association between opioid abuse/dependence and outcomes in hospitalized patients has not been well studied. Congestive heart failure (HF) is the fourth most common cause of hospitalization in the United States. The purpose of this study was to examine the effect of opioid abuse/dependence on outcomes in patients hospitalized with HF. We queried the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Overall, 12 studies reported prevalence of respiratory disease with non-using comparator groups [9,10,19,20,23,25,26,[30][31][32][33][34]. Two of the included studies met criteria on all quality domains applicable; individual study quality scores are presented in Table 1.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…Overall, 12 studies reported prevalence of respiratory disease with non-using comparator groups [9,10,19,20,23,25,26,[30][31][32][33][34]. Two of the included studies met criteria on all quality domains applicable; individual study quality scores are presented in Table 1.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…Opioid use has also been associated with adverse respiratory outcomes, 32,33 but not heart failure in other patient populations. 34,35 Both the prevalence and dose of opioids increased significantly from the 0 to 9 age group to the 10 to 19 year age group, implying that the vaso-occlusive pain increases during the second decade of life in the SCD patients. The prevalence of opioid use slowly declined with increasing age after reaching the peak at the 20 to 29 years group, especially in the age group of 50+ years old ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to high‐dose morphine and its active metabolite, morphine‐6‐glucuronide, has been suggested to increase the risk of ACS in SCD patients, which is consistent with our observation. Opioid use has also been associated with adverse respiratory outcomes, but not heart failure in other patient populations …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current literature on HF patients with OUD is mixed. Some studies have found higher readmissions and hospitalization rates with OUD, while others have found no effects [ 4 , 10 ]. Meanwhile, studies have described CUD as an independent predictor for the development of HF [ 11 ].…”
Section: Discussionmentioning
confidence: 99%